Tindak Tutur Ilokusi pada Interaksi Jual Beli Pedagang di Pekan Selasa Desa Laut Dendang - Miftah Maulidya1; Nadra Amalia (Medan Resource Center, 2023)
This study examines the illocutionary speech acts that occur in the buying and selling interactions of traders and buyers in Pekan Selasa Laut Dendang. The purpose of this study was to describe illocutionary speech acts in the interaction of buying and selling traders in Pekan Selasa Laut Dendang. The data in this study is the interaction of the seller and the buyer which is indicated to contain illocutionary speech acts. The method used is descriptive method. The research instrument was carried out with observation and documentation guidelines. The technique used to analyze the data obtained in the study is an interactive analysis technique. The result of this study is the presence of illocutionary speech acts used in the interaction of buying and selling traders in the Pekan Selasa Laut Dendang. It was found that there were 35 illocutionary speech act data on trading interactions of traders in the Pekan Selasa Laut Dendang with details of 8 representative speech act speech, 4 commissive speech act speech, 14 directive speech act speech, 5 expressive speech act, and 4 declarative speech acts.